To Compare Thread Technique Versus Aspiration Plus Steroid Injection Of Wrist Ganglion In Terms Of Frequency Of Recurrence - Basit, Abdul; Abbasi, Salman Habib; Farooq, Muhammad; Shah, Fazal Hussain (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the recurrence of wrist ganglion following thread technique versus aspiration plus steroid injection. Methods: This was a Randomized controlled trial conducted in the Department of Surgery. HIT Hospital, Taxila from June 2020 to December 2020. Sixty patients were randomized into two equal groups A and B after clinical diagnosis of wrist ganglion. Informed written consent was obtained after informing all pros and cons of the procedure. The thread technique was done in group A while in group B methyl prednisolone acetate 40 mg/ml was injected after aspiration. The patients were followed 2 weeks, 6 weeks, 3 months, and 6 months. The clinical examination was done to see the possible recurrence. Results: The mean age of the participants was 29.30 ± 6.0 years. The mean duration of ganglia was 19.33 ± 8.35 months. The location of ganglia was 37 (61.7%) dorsal and 23 (38.3%) volar. The male-to-female ratio was 22 (36.7%): 38 (63.3%). Collectively, the frequency of recurrence was 6 (10%), 10 (16.7%), 12 (20%) and 16 (26.7%) at 2 weeks, 6 weeks, 3 months, and 8 months respectively. There was no difference between groups A and B in terms of age, gender, location, and duration of disease (p values 0.401, 0.592, 0.791, 0.783 respectively). The frequency of recurrence was significantly different among groups at 6 months i.e. 12 (40.0%) in group A versus 4 (13.3%) in group B (p-value 0.020). Conclusion: The thread technique of wrist ganglia is superior to steroid injection in terms of recurrence. The RCTs with a larger sample size and prolonged follow-up would provide more insight into this subject.